A MASS IMAGING TECHNIQUE REVEALED A RENO-PROTECTIVE EFFECT OF THE XANTHINE OXIDASE INHIBITOR FEBUXOSTAT IN THE ISCHEMIC KIDNEY BY PROMOTING ATP RECOVERY IN THE CORTEX. (June 2018) - Miyashita, K.; Fujii, K.; Kubo, A.; Sato, M.; Hagiwara, A.; Inoue, H.; Ryuzaki, M.; Endo, S.; Uto, A.; Suematsu, M.; Itoh, H.
Abstract : Objective: The kidney has different energy metabolism depending on the region. However, the distribution of phosphorylated adenosine (ATP, ADP and AMP) and their alteration after transient ischemia have not been known due to the technical difficulties. Design and method: Imaging mass spectrometry (IMS) with metabolome analysis is a novel technique to quantify the small metabolites in the tissues. We performed the IMS analysis in the ischemic kidney after transient ischemia by renal artery clipping. Results: In the normal kidney, ATP was significantly rich in both the cortex and outer medulla. After transient ischemia, ATP in the cortex degraded and the energy charge value decreased within a minute. ATP in the inner medulla did not decrease within a minute and needed 10 minutes to start decreasing. After the 10 minutes of ischemia, total adenylates decreased in the cortex, although the decrease in energy charge value was homogeneous in the kidney. During the 24 hours reperfusion after 10 minutes ischemia, restoration of total adenylates in the cortex was not sufficient. Febuxostat is a xanthine oxidase inhibitor which might promote reuse of hypoxanthine as a progenitor of adenylates and therefore might improve the restoration of total adenylates and ATP after transient ischemia. The administration of febuxostat in accordance with the reperfusion period supported the restoration of ATP level in the cortex and improved renal function which was impaired by transient ischemia. Conclusions: In these ways, IMS revealed the region-specific alteration of phosphorylated adenosine the ischemic kidney and the novel effect of febuxostat on the restoration of total adenylates and ATP in the cortex after transient ischemia.